Peran Produk Halal dan Ramah Lingkungan dalam Mewujudkan Green Economy di Industri Syariah FAS FOOD Desa Duriwetan - Anggilah Mawarni; Syuhada; Intan Ayu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The concept of green economy is now a major concern as a solution to overcome environmental challenges and sustainable development. In the sharia industry, the implementation of green economy is in line with Islamic principles that emphasize halal, sustainability, and ethics. This study aims to examine the role of halal and environmentally friendly products in realizing a green economy in the FasFood business in Duriwetan Village. The method used is a qualitative approach through interviews with business actors and consumers. The results of the study indicate that the role of FasFood products has met halal standards, as evidenced by official halal certification and high awareness of business actors regarding raw materials and production processes. Halal labels have been shown to significantly influence consumer decisions. On the other hand, the role of environmentally friendly principles has not been implemented properly by FasFood business actors in Duriwetan Village because they still use plastic-based packaging and food waste management, with this study, FasFood business actors in Duriwetan Village will try to start adopting environmentally friendly principles such as reducing plastic use and managing food waste. In conclusion, the integration of halal and environmentally friendly principles in the sharia industry of FasFood in Duriwetan village has made a real contribution to supporting the green economy. However, policy support and education are needed to improve more comprehensive implementation.